Anonymously Provided Sperm and the Constitution - Byrn, Mary Patricia; Ireland, Rebecca (Columbia Journal of Gender and Law, 2012)
Obtaining sperm to use in Assisted Reproductive Technology (“ART”) is relatively simple.’ Hospitals, clinics, and sperm banks throughout the United States are in the business of selling sperm from literally thousands of men.’ This does not mean, however, that becoming a sperm provider is easy. When a man decides to sell his sperm, he must first undergo an involved screening process to test for genetically inheritable and infectious diseases that could be transmitted through his sperm. The screening process is purposefully rigorous, and sperm banks boast that the effect of these stringent guidelines is to eliminate ninety-nine percent of potential providers.’ Once a man is approved to provide sperm, he contracts with the sperm bank to supply sperm for a specified period of time and designates himself as either an anonymous or open-identity sperm provider.